The Manaus Declaration: Current Situation of Histoplasmosis in the Americas, Report of the II Regional Meeting of the International Histoplasmosis Advocacy Group (2019)
Purpose of Review: The aim of this report is to summarize the conclusions of the II Regional Meeting on Histoplasmosis in the Americas held in Manaus, Brazil, on March 22–24, 2019. Recent Findings: Persons living with advanced HIV are at high risk for developing histoplasmosis. Clinical signs and symptoms of this disease are often non-specific, making it difficult to establish a diagnosis. Although with the recent technological advances, in vitro diagnostics and medicines for histoplasmosis are often not available in many regions around the world. In addition, histoplasmosis is often not included in HIV care and treatment programs, resulting in inadequate health system planning and missed opportunities to save lives. Summary: The II Regional Meeting on Histoplasmosis in the Americas gathered a multidisciplinary audience. Developed recommendations to be included in the WHO guidelines for diagnosis and treatment of histoplasmosis in advanced HIV were the product of this meeting, and guidelines are aimed to be published in early 2020. © 2019, This is a U.S. Government work and not under copyright protection in the US; foreign copyright protection may apply.